Contractual Risk and Consumer Protection in Salam Transactions: A Case Study of Fruit Trading in Aceh Besar, Indonesia - Salamah, Ummi; Arifin, Muhammad; Farma, Junia (Universitas Syiah Kuala, 2025)
This study examines the implementation of the salam contract in fruit trading practices at the Lambaro Central Fruit Market, Aceh Besar, with a particular focus on assessing its compliance with the principles of fiqh muamalah and identifying gaps between Islamic legal norms and actual market practices. Employing a qualitative descriptive approach, the data were collected through observations, structured interviews with five fruit sellers and five distributors, as well as supporting documentation. The findings indicate that salam transactions are commonly practiced through a pre-order system with full advance payment, accompanied by explicit agreements regarding fruit type, quantity, delivery time, and delivery locationdemonstrating adherence to most core requirements of the salam contract. However, inconsistencies arise in relation to accountability for damaged goods, as distributors generally do not provide compensation for spoiled or non-conforming fruits, leaving sellers to bear the entire risk of loss. This practice contradicts Islamic legal principles, which stipulate that sellers remain responsible for the goods until they reach buyers in the agreed-upon condition. The study concludes that although the salam mechanism helps maintain continuity in the fruit supply chain, it has not fully achieved the principles of fairness, justice, and consumer protection mandated in Islamic law. To ensure alignment with sharia objectives, the study recommends the establishment of written contractual agreements, standardized procedures for quality inspection at delivery, and clear liability regulations to protect transaction parties with weaker bargaining positions. The novelty of this research lies in its empirical examination of salam implementation within the largest traditional fruit market in Aceh Besar through real supply-chain interactions, rather than relying solely on normative legal analysis.